Calcium signaling in membrane repair. (September 2015) - Cheng, Xiping; Zhang, Xiaoli; Yu, Lu; Xu, Haoxing
Abstract: Resealing allows cells to mend damaged membranes rapidly when plasma membrane (PM) disruptions occur. Models of PM repair mechanisms include the "lipid-patch", "endocytic removal", and "macro-vesicle shedding" models, all of which postulate a dependence on local increases in intracellular Ca 2+ at injury sites. Multiple calcium sensors, including synaptotagmin (Syt) VII, dysferlin, and apoptosis-linked gene-2 (ALG-2), are involved in PM resealing, suggesting that Ca 2+ may regulate multiple steps of the repair process. Although earlier studies focused exclusively on external Ca 2+, recent studies suggest that Ca 2+ release from intracellular stores may also be important for PM resealing. Hence, depending on injury size and the type of injury, multiple sources of Ca 2+ may be recruited to trigger and orchestrate repair processes. In this review, we discuss the mechanisms by which the resealing process is promoted by vesicular Ca 2+ channels and Ca 2+ sensors that accumulate at damage sites.